Burn Contracture In Children : A Case Series - Andly Resando Mallo; Mendy J. Hatbie; Maximillian Christian Oley (Jurnal sosial dan sains, 2024)
Background: Contractures after burns are the most common complication, should be prevented, and if they occur, are more difficult to treat. In developing countries such as Indonesia, it is more difficult for children with burns to get treatment for acute burns, resulting in joint contractures and soft tissue weakness. On the other hand, if contractures have already appeared, various methods such as z-plasty, multiple s-plasty, and even reconstructive flaps can be performed, especially in persistent contractures. Purpose: This study aims to find out several types of therapy and surgical management that can be carried out in contracture patients. Method: This study uses a qualitative research method with a case study approach. The data collection techniques used in this study are observation, medical record study, and literature study. The data that has been collected is then analyzed through three stages, namely data reduction, data presentation, and conclusion drawing. Results: The results of the study show that early management of burns in children can provide a better prognosis, if contractures have occurred, treatment requires several stages and the function cannot return to normal and aesthetics can be improved according to the difficulty of the burn. contracture. Conclusion: Research on contractures due to burns in children shows that early management can provide a better prognosis. If contractures have formed, treatment requires several stages and often cannot completely restore normal function.